Educational Leave as a Time Resource for Participation in Adult Learning and Education (ALE) - Rüter, Fabian; Martin, Andreas; Schrader, Josef (Frontiers in Psychology, 2020)
The study investigates effects of the implementation of a law on educational leave in Germany on individual participation in adult learning and education (ALE). In 2015, the federal state of Baden-Württemberg introduced such a law called the Bildungszeitgesetz, legitimating an exemption for eligible employees of up to five days per year with continued payment of salary. Explaining participation in ALE is a central subject of educational research at national and international level. Current theoretical assumptions of rational choice and empirical findings of educational and socio-statistical research suggest that in the general population, individuals’ availability of time affects the decision to participate and therefore determines participation in ALE. However, current academia mainly discusses time as either a prerequisite for learning activities or as an observable outcome of participation and not as an explanatory factor. Furthermore, since current research remains on a descriptive level regarding influences of time on participation in ALE, no causal effects of the availability of time on participation are explained. Hence, our study addresses this research gap by investigating effects of educational policy interventions such as the Bildungszeitgesetz on participation in ALE. Policy interventions are ideally suited to examine the significance of time resources for participation, as the implementation of the Bildungszeitgesetz provides a specific timeframe for employees to participate in ALE outside of their working time. Drawing on data from the German National Educational Panel Survey (NEPS), we employ a difference-in-differences estimation strategy with propensity score matching and instrumental variable to identify the direct causal effect of the implementation of the Bildungszeitgesetz on participation in ALE. This combination towards causal inference controls for observed and unobserved baseline differences as well as heterogeneous treatment effects. The results reveal no significant but heterogeneous treatment effect of the implementation of the Bildungszeitgesetz on individual participation in ALE. Contrary to our theoretical assumptions of rational choice, we cannot confirm the hypothesis that the availability of time resources due to the implementation of the Bildungszeitgesetz causes a positive effect on participation in ALE. Furthermore, the result reveal that the implementation causes decreasing participation rates for younger adults, women and significantly for migrants.